PENGARUH NILAI PELANGGAN DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN DALAM MENINGKATKAN RETENSI PELANGGAN PADA BATIK MEREK MERAK MANIS DI SURAKARTA - LAKSONO SUMARTO (JURNAL WIDYA GANECWARA, 2015)
The expected goals of this study were (1) to analyze and measure the impact of customer value and brand image to customer satisfaction (2) To analyze and measure the impact of customer value and brand image on customer retention. (3) To analyze and measure the influence of customer satisfaction on customer retention (4) To analyze and measure customer satisfaction in mediating the effects of customer value and brand image on customer retention. The study was conducted at the customer's Batik Merak Manis in Surakarta. The population in this study are all consumers who buy batik silk crepe smooth. The number of samples specified by 40 respondents with a sampling technique using purposive sampling with certain criteria. In this study, researchers used a type of quantitative data from primary and secondary sources. The data analysis techniques using path analysis with t-test, F-test, analysis of determination. The results of the data analysis it was found that (1) there is a positive and significant impact of customer value and brand image to customer satisfaction. (2) There is a positive and significant impact of customer value and brand image on customer retention. (3) Customer satisfaction has positive influence on customer retention Batik Merak Manis. (4) Customer satisfaction mediates the effects of customer value on the retention of customers with smaller correlation when compared to the direct effect of customer value on customer retention. However, customer satisfaction in the brand image to mediate its effect on retention is greater than the direct effect of brand image on customer retention. Based on the value of the coefficient of determination that have a positive value of 0.769 indicates that customer retention Sweet Peacock in Surakarta batik can be explained by the variables of customer value, brand image and customer satisfaction variable as a mediating variable only by 76.90% while the remaining 23.10% explained by the study variables.